PELATIHAN PENGEMBANGAN MANAJEMEN SUMBER DAYA MANUSIA DAN KUALITAS PELAYANAN UNTUK MENINGKATKAN PRODUKTIVITAS PADA PABRIK KUDA TANDANG OLAHAN SNACK KOTA SUMEDANG - Pramesti, Hasti; Dewi, Ade Nurhayati; Mawardi, Amna; Chrisulianti, Rizki; Winarni, Riani (LPPM Universitas Bina Bangsa, 2025)
This community service aims to develop human resource (HR) management and improve service quality to increase productivity at Kuda Tandang Factory, a traditional snack producer in Sumedang City. Since its establishment in 2013, the company has faced challenges in HR management and service quality that affect production efficiency and product quality. With increasingly tight competition in the processed food sector, Kuda Tandang Factory needs to develop HR management strategies and improve services to maintain competitiveness in the market. The proposed program includes HR needs analysis, technical and managerial training, development of a performance management system, and periodic performance evaluation. The results of the community service show significant improvements in employee skills, operational efficiency, and service quality, which have an impact on increasing productivity by up to 20% and increasing customer satisfaction. This community service highlights the importance of effective HR management and good service quality to drive competitiveness in the SME sector, and offers a model that can be adapted by other SMEs in the processed food industry.